KECERDASAN MENGGALI INFOMASI POLITIK DI MEDIA DIGITAL - Salman Salman; Syaifuddin Syaifuddin (Avant Garde, 2018)
This study aims to determine people's understanding of information and political messages that are scattered in the digital world. The development of digital technology has brought about very significant changes in the world of communication today, in connection with information obtained by the public. The spread of information on digital media cannot be dammed, any information can be obtained easily, anyone can access that information without any limitations. The information is presented from very simple to complex, from educating information to information that spreads hatred easily available. This research use desciptive qualitative approach. The results of this study indicate that there is still a very low ability of the community to choose and distinguish between correct political information and false information or "hoaxes". The audience thinks, every information that is available is useful information, although sometimes the information is false information or "hoaxes".